Motion Value Smoothly Cimande Pencak Silat in Preserving Cultural Identity and Character Building - Lestari, Rahayu; Jaeni, Jaeni; Fussalam, Yahfenel Evi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the local wisdom values embodied in the Salancaran movements of Cimande Pencak Silat and their relevance to strengthening character education in schools. Salancaran movements, as one of the basic sequences in the Cimande style, function not only as self-defense techniques but also contain philosophical messages reflecting Sundanese cultural values such as patience, perseverance, self-control, vigilance, and respect. Using a qualitative approach utilizing ethnographic and ethnopedagogical methods, this study explores the cultural meanings inherent in Salancaran practices through field observations, interviews with Cimande practitioners, and document analysis. The results indicate that the values within the Salancaran movements are strongly linked to the dimensions of the Pancasila Student Profile, thus providing potential as a source for contextual character learning within the Independent Curriculum. The integration of these local cultural values can enrich culture-based educational strategies while strengthening student identity amidst the challenges of globalization. This research provides theoretical contributions to the development of ethnopedagogical studies and practical benefits for education through a conceptual model for utilizing local wisdom as a source for character learning.